Effects of energy supplementation on lamb production of Javanese Thin-Tail ewes - Reese, A.A.; Handayani, S.W.; Ginting, S.P.; Sinulingga, W.; Reese, G.R.; Johnson, W.L. (1990)
A 3-yr study was conducted in North Sumatra, Indonesia, as part of an evaluation of the feasibility of integrating sheep and rubber production. The objective was to evaluate the effects of increaing energy supplementation on reproduction and other performance traits of Javanese Thin-tailed sheep grazing forage under 8- and 14-yr-old rubber trees. The control group was unsupplemented. The medium group was supplemented with high-energy feeds at 1 percent of the flock body weight, with the low and high groups receiving 60 or 140 percent of the daily energy provided by the medium-group diet. Supplements provided 1.2 g protein/kg body weight; 158 lambs were born to the 162 ewes in the 1st yr of the study. Preweaning mortality was reduced (P 0.01) by supplementation (45, 12, 3 and 12 percent for the control, low, medium and high groups resp.). During the 3 yr, litter size was highest (P 0.01) in the high group (1.33, 1.31, 1.34 and 1.71 for ewes on the 4 diets resp.). Observed repeatability of litter size of individual ewes in all treatment groups for the first 3 parities was higher (P 0.01) than would be expected if litter size were a random event. Of the lambs born in the 1st yr, weight of lamb weaned per ewe joined averaged 3.1, 7.8, 7.3 and 9.8 kg. At prevailing prices, only the high supplement level was profitable compared with the control. For the high group, the added return from the sale of lambs born in the 1st yr was 120 percent of the added cost of supplementing the ewes until all the lambs were weaned (15 months). Response of sheep to the high level of energy supplementation, especially with regard to litter size, indicates that supplementing sheep grazing in rubber plantations at a high level can be profitable.